Smart Farming System untuk Tanaman Hidroponik Berbasis Internet of Things - Suryo Adi Wibowo; Kartiko Ardi Widodo; Deddy Rudhistiar (Jurnal Bumigora Information Technology (BITe), 2023)
Background: The tropical climate that Indonesia has, with the sun shining all year round, is the advantage of Indonesia being on the equator. This tropical climate causes thousands of types of flora and fauna to grow beautifully and thrive in Indonesia as well as plants that can be cultivated, such as vegetables. It is not wrong if, at this time, vegetable plants are the target of flora hobbyists. Currently, several types of vegetable crops can be developed using the hydroponic or vertical garden method so that they can generate income even on limited land. This reason has made many flora lovers develop vertical gardens en masse or for hobby purposes. The problems that are often faced by these hobbies include the maintenance process and even delays in providing nutrients to the planting medium.Objective: The researchers designed a smart farming system for hydroponic plants based on the Internet of Things (IoT) to facilitate the maintenance of vertical garden plants.Methods: The method used in this research was fuzzy logic and the Internet of things.Result: The results of system testing found that the average deviation of the TDS sensor was 3.229% and that of the Ph meter sensor was 4.081%. Using a smart hydroponic system can increase the growth of mustard plants by 1.775%.Conclusion: IoT-based smart farming systems for hydroponic plants have been successfully developed.